Lidar-radar for underwater target detection using a modulated sub-nanosecond Q-switched laser. (October 2021) - Li, Guangying; Zhou, Qiang; Xu, Guoquan; Wang, Xing; Han, Wenjie; Wang, Jiang; Zhang, Guodong; Zhang, Yifan; Yuan, Zhi'an; Song, Sijia; Gu, Shangtai; Chen, Fubin; et al.
Highlights: The cooperation of the streak tube imaging and modulated laser source for underwater target detection experiments is the first attempt in this field. The clear 3-D and 4-D images of the target underwater across 20 m are obtained with the spatial resolution of 9 mm. The signal-to-clutter ratio (SCR) of echo signal can be vastly enhanced using the hybrid lidar-radar system Abstract: Here we report on a modulated sub-nanosecond lidar-radar for underwater target detection. The modulated laser source is consisted of a 1064 nm master oscillator power amplifier (MOPA) and a frequency-doubling module, outputting pulse energy of 178.1 mJ at 1064 nm with 0.76 ns pulse duration and 87.6 mJ at 532 nm. By using a Fabry–Pérot cavity containing a KTP crystal and two reflectors, the 532 nm laser pulse is modulated into the burst mode with a repetition rate of 500 MHz. A streak tube camera is used as the signal receiving apparatus. An underwater target detection experiment has been carried out. The results indicate that this lidar-radar could emit a stable and powerful modulated signal, which greatly increases the underwater detection range. The cooperation of the streak tube imaging and modulated laser source for underwater target detection experiments is the first attempt in this field. The clear 3-D and 4-D images of the target underwater across 20 m are obtained in the experiments and the spatial resolution of 9 mm can be achieved.